Knygotyra (Book Studies) of the Last Decade: Traditions and Modernity - Bliūdžiuvienė, Nijolė; Navickienė , Aušra (Knygotyra, 2024)
The scholarly journal Knygotyra is now entering into its seventieth year of establishment. The periods of 1970 –1998 and 1999–2012 have already been analysed in the articles by Vanda Stonienė and Alma Braziūnienė in terms of organisation, structure, content and other aspects. The aim of this article is to compare the continuity of the tradition of Knygotyra between the periods already studied and the years 2013–2023, and to identify the changes that have taken place in the last decade, which may determine the journal’s future. This article examines the organisational aspects of Knygotyra which reflect the journal’s periodicity, volume, circulation, access, funding, and editorial board membership, as well as the journal’s structure, topics, publication types, language, and authorship. During the analysed period, the scientific journal Knygotyra not only maintained its identity, but also accepted the changes and adapted to them. Over the last decade, it has become a Diamond (Platinum) Open Access international journal, listed in the Elsevier Scopus and Clarivate Analytics international databases. The editorial board has been formed and renewed, whereas the geographical coverage of authors and the thematic structure of publications have been extended.